Potassium Regulation in Medaka (Oryzias latipes) Larvae Acclimated to Fresh Water: Passive Uptake and Active Secretion by the Skin Cells. Issue 1 (December 2017) - Horng, Jiun-Lin; Yu, Li-Lu; Liu, Sian-Tai; Chen, Po-Yen; Lin, Li-Yih
Abstract Molecular mechanisms of Na+, Cl−, and Ca2+ regulation in ionocytes of fish have been well investigated. However, the regulatory mechanism of K+ in fishes has been largely unknown. In this study, we investigated the mechanism of K+ regulation in medaka larvae acclimated to fresh water. Using a scanning ion-selective electrode technique (SIET) to measure the K+ fluxes at skin cells, significant K+ effluxes were found at ionocytes; in contrast, significant K+ influxes were found at the boundaries between keratinocytes. High K+ water (HK) acclimation induced the K+ effluxes at ionocytes and suppressed the K+ influxes at keratinocytes. The K+ effluxes of ionocytes were suppressed by VU591, bumetanide and ouabain. The K+ influxes of keratinocytes were suppressed by TAP.In situ hybridization analysis showed that mRNA ofROMKa was expressed by ionocytes in the skin and gills of medaka larvae. Quantitative PCR showed that mRNA levels ofROMKa andNKCC1a in gills of adult medaka were upregulated after HK acclimation. This study suggests that medaka obtain K+ through a paracellular pathway between keratinocytes and extrude K+ through ionocytes; apical ROMKa and basolateral NKCC1a are involved in the K+ secretion by ionocytes.